Slamming into Spirituality: Using Nature Poems and Inaq Elements to Humanise Gifted Learners - Normazla Ahmad Mahir; Zarina Ashikin Zakaria; Norhaili Massari; Mohd Muzhafar Idrus; Suzanah Selamat; Lubna Abd Rahman; Myra Aidrin Mohd Ali (Universiti Sains Islam Malaysia, 2026)
International Conference of Language & Education (iLEC2025): Empowering Language and Education to Develop Madani Generation in the Era of Artificial Intelligence (AI) 17 & 18 November 2025 Organized by Universiti Sains Islam Malaysia